Cerebrospinal fluid analysis in dengue in a tertiary care center - Dhar, Srikant Kumar; Rout, Udaybhanu; Suse, Naqash Nadar; Arve, Nikhil Rajendra; Yennam, Naresh; Swain, Rakesh Keshari (International Journal of Research in Medical Sciences, 2020)
Background: Clinical profile of dengue is variable including neurological manifestations like encephalopathy and encephalitis which are not being reported very frequently. This study is an attempt to know the cerebrospinal fluid (CSF) finding in dengue infected patients with neurological manifestations in a tertiary care hospital Eastern Odisha. Methods: Study conducted from August 2018 to July 2019 comprising of 100 dengue seropositive (NS1/IgM/IgG) patients of age >15 years in IMS and SUM Hospital. Results: A total of 100 (66 boys and 34 girls) hospitalised patients (Age >15 years) diagnosed as dengue were enrolled in our study. Total 20 cases Cerebrospinal fluid analysis has been done in which we found 70% (13 cases) unclassified viral meningitis, 15% (3 cases) bacterial meningitis, 5% (1 case) tuberculous meningitis, 5% (1 case) herpes encephalitis and 5% (1 case) Japanese encephalitis. Neurological manifestations in all dengue sero positive cases (100) found 30% headache, 18% altered sensorium, 5% seizure, 4% syncope, 3% papilloedema, 1% CN palsy and 11% meningeal signs. Conclusions: Dengue meningoencephalitis must be thought of in differentials of all febrile encephalopathy. This study brings out the incidence of different meningoencephalitis on the bases of CSF analysis including coinfections. So in dengue patients with neurological manifestation should do CSF analysisfor better outcome of a disease.